Economic Selection Indices: The Best Tool for Dairy Cattle Selection: AN353, 3/2019 - Peñagaricano, Francisco (EDIS, 2019)
An economic selection index combines multiple traits into a single value, facilitating the identification of the best animals. This new 3-page document discusses economic selection indices, their changes in the US, and a 2018 update. Written by Francisco Peñagaricano, and published by the UF/IFAS Department of Animal Sciences, March 2019. http://edis.ifas.ufl.edu/an353